PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA SISWA SEKOLAH DASAR - Asih Sugiharti; Wiputra Cendana (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
This learning improvement research is entitled “Application of Contextual Teaching and Learning Model to improve learning outcomes in Indonesian language subjects of elementary school students”. The problem in this class action research is, can the Contextual Teaching and Learning model improve the level of student learning outcomes? The purpose of this classroom action research is to improve the learning outcomes of elementary school students in Indonesian language subjects through the Contextual Teaching and Learning approach). The implementation of this learning improvement research uses a qualitative descriptive method, carried out in 2 cycles, which in each cycle is divided into 4 stages, namely: planning, implementation, observation and reflection. The subjects of this study were third grade students of SD IT Wihdatul Ummah totaling 23 students. The measuring instrument used is a learning outcome test and indicators compiled into an observation sheet. It is a clue to success in this study if the average score of the indicators is 70% and the students who are the subjects of the study have achieved a minimum score of 70 (KKM from the School). The findings show an increase in student learning outcomes. In the first cycle action, the percentage of students who reached the minimum completeness criteria was 52.17% and in the second cycle action, the percentage of students' minimum completeness criteria reached 78.26%. This is based on the data obtained in cycle I, the total number of students reaching the minimum completeness criteria was 12 students and after the action of cycle II the number of students reaching the minimum completeness criteria increased by 18 students out of 23 students.